The Development of Indonesian Language Learning Media Based on Augmented Reality For Fifth Grade of Elementary School - Dudu Suhandi Saputra, Sigit Vebrianto Susilo, Tita Mulyawati, Yunus Abidin, Reza Rachmadtullah, Rasmitadila, Nopiana (International Journal of Advanced Science and Technology, 2020)
This study aims to produce Indonesian language learning media for fifth Grade students of Primary Schools in Majalengka Regency, West Java Province with a total of 50 student respondents. The research method used is Development Research with the Borg and Gall model. The results of the study of the validation of aspects of the material, media, and language show that the Indonesian language learning media based on augmented reality is valid. In the individual test and small group test stages, students who are the subjects of the research respond very well to the Indonesian language learning media based on augmented reality that is used. To see the effectiveness of the product being developed continued with a large group test with 50 students. Based on the results of the study it can be concluded that the Indonesian language learning media based on augmented reality developed in this study proved to be valid, practical, and had a potential effect on student learning outcomes in learning Indonesian in Elementary Schools. Keywords: Learning Media, augmented reality, development of media